Effects of Electronic Cigarette Liquid Nicotine Concentration on Plasma Nicotine and Puff Topography in Tobacco Cigarette Smokers: A Preliminary Report - Lopez, Alexa A. (Nicotine Tob Res, 2016)
INTRODUCTION: Electronic cigarettes (ECIGs) aerosolize a liquid that usually contains propylene glycol and/or vegetable glycerin, flavorants, and the dependence-producing drug nicotine in various concentrations. This study examined the extent to which ECIG liquid nicotine concentration is related to user plasma nicotine concentration in ECIG-naïve tobacco cigarette smokers. METHODS: Sixteen ECIG-naïve cigarette smokers completed four laboratory sessions that differed by the nicotine concentration of the liquid (0, 8, 18, or 36mg/ml) that was placed into a 1.5 Ohm, dual coil “cartomizer” powered by a 3.3V battery. In each session, participants completed two, 10-puff ECIG use bouts with a 30-second inter-puff interval; bouts were separated by 60 minutes. Venous blood was sampled before and after bouts for later analysis of plasma nicotine concentration; puff duration, volume, and average flow rate were measured during each bout. RESULTS: In bout 1, relative to the 0mg/ml nicotine condition (mean = 3.8ng/ml, SD = 3.3), plasma nicotine concentration increased significantly immediately after the bout for the 8 (mean = 8.8ng/ml, SD = 6.3), 18 (mean = 13.2ng/ml, SD = 13.2), and 36mg/ml (mean = 17.0ng/ml, SD = 17.9) liquid concentration. A similar pattern was observed after bout 2. Average puff duration in the 36mg/ml condition was significantly shorter compared to the 0mg/ml nicotine condition. Puff volume increased during the second bout for 8 and 18mg/ml conditions. CONCLUSIONS: For a given ECIG device, nicotine delivery may be directly related to liquid concentration. ECIG-naïve cigarette smokers can, from their first use bout, attain cigarette-like nicotine delivery profiles with some currently available ECIG products. IMPLICATIONS: Liquid nicotine concentration can influence plasma nicotine concentration in ECIG-naïve cigarette smokers, and, at some concentrations, the nicotine delivery profile of a 3.3V ECIG with a dual coil, 1.5-Ohm cartomizer approaches that of a combustible tobacco cigarette in this population. Finding a product that delivers nicotine as effectively as a tobacco cigarette, as we report here, may be essential for smokers who want to replace completely their combustible tobacco cigarettes with ECIGs.